Comparison Effects and Dielectric Properties of Different Dose Methylene-Blue-Doped Hydrogels - Yalcin, O.; Coskun, R.; Okutan, M.; Ozturk, M. (AMER CHEMICAL SOC, 2013)
The dielectric properties of methylene blue (MB)-doped hydrogels were investigated by impedance spectroscopy. The real part (epsilon') and the imaginary part (epsilon '') of the complex dielectric constant and the energy loss tangent/dissipation factor (tan delta) were measured in the frequency range of 10 Hz to 100 MHz at room temperature for pH 5.5 value. Frequency variations of the resistance, the reactance, and the impedance of the samples have also been investigated. The dielectric permittivity of the MB-doped hydrogels is sensitive to ionic conduction and electrode polarization in low frequency. Furthermore, the dielectric behavior in high-frequency parts was attributed to the Brownian motion of the hydrogen bonds. The ionic conduction for MB-doped samples was prevented for Cole-Cole plots, while the Cole-Cole plots for pure sample show equivalent electrical circuit. The alternative current (ac) conductivity increases with the increasing MB concentration and the frequency.
Keywords: DRUG-DELIVERY; ELECTRICAL-CONDUCTIVITY; RADIATION SYNTHESIS; IMPEDANCE SPECTROSCOPY; SENSITIVE HYDROGELS; COMPLEX IMPEDANCE; POLYMER; ACID; RELAXATION; POLYSACCHARIDE; Biophysics; Chemistry